Sanguisorbae Radix Suppresses Colorectal Tumor Growth Through PD-1/PD-L1 Blockade and Synergistic Effect With Pembrolizumab in a Humanized PD-L1-Expressing Colorectal Cancer Mouse Model - Lee, Eun-Ji; Kim, Ji Hye; Kim, Tae In; Kim, Yeon-Ji; Pak, Malk Eun; Jeon, Chang Hyun; Park, Yeo Jin; Li, Wei; Kim, Young Soo; Choi, Jang-Gi; Chung, Hwan-Suck (Frontiers in Immunology, 2021)
Immune checkpoints such as programmed death-1 (PD-1) have been proven as antitumor targets by enhancing cytotoxic T cell activity. All immune checkpoint blockades are antibody therapeutics that have large size and high affinity, as well as known immune-related side effects and low responses. To overcome the limitation of antibody therapeutics, we have explored PD-1/PD-L1 (programmed death-ligand 1) blockades in traditional oriental medicine, which has a long history but has not yet studied PD-1/PD-L1 blockades. Sanguisorbae Radix extract (SRE) blocked PD-1 and PD-L1 binding in competitive ELISA. SRE effectively inhibited the PD-1/PD-L1 interaction, thereby improving T cell receptor (TCR) signaling and the NFAT-mediated luciferase activity of T cells. SRE treatment reduced tumor growth in the humanized PD-L1 MC38 cell allograft humanized PD-1 mouse model. Additionally, the combination of SRE and pembrolizumab (anti-PD-1 antibody) suppressed tumor growth and increased infiltrated cytotoxic T cells to a greater extent did either agent alone. This study showed that SRE alone has anticancer effects via PD-1/PD-L1 blockade and that the combination therapy of SRE and pembrolizumab has enhanced immuno-oncologic effects.